Grass-thrips of the genus Oelschlaegera (Thysanoptera: Thripidae), with the first description of a male - Fekrat, Lida; Hosseininejad, Marziyeh; Derakhshan, Ali; Minaei, Kambiz (Zootaxa, 2016)
The Chirothrips-like species are grass-living members of the Thysanoptera family Thripidae. All of these species were assigned to the genus Chirothrips Haliday (1836) until Hood (1954) erected Agrostothrips for a single species from South Africa, and Knechtel (1960) described a new monotypic genus Ereikethrips from Romania. An extensive identification key to the 52 species of Chirothrips then known was published by zur Strassen (1960), and the generic classification remained stable for the next 30 years. However, Bhatti (1990) erected five new genera for several species of this genus (Afrothripella, Arorathrips, Konothrips, Longothrips and Oelschlaegera). Bhatti also included three further species in Agrostothrips, but Minaei & Mound (2010) regarded Agrostothrips as a synonym, and returned all four species to Chirothrips. In the most recent study of the group, Nakahara & Foottit (2012) added one monobasic genus, Unilobothrips, and provided an identification system to the 36 Chirothrips-group species known from the Americas. Thus, eight genera are currently included in this genus group (Table 1).